2015
DOI: 10.1071/zo14052
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of beak and feather disease virus in wild Platycercus elegans: comparison of three tissue types using a probe-based real-time qPCR test

Abstract: The detection of avian viruses in wild populations has considerable conservation implications. For DNAbased studies, feathers may be a convenient sample type for virus screening and are, therefore, an increasingly common technique. This is despite recent concerns about DNA quality, ethics, and a paucity of data comparing the reliability and sensitivity of feather sampling to other common sample types such as blood. Alternatively, skeletal muscle tissue may offer a convenient sample to collect from dead birds, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 53 publications
2
44
2
Order By: Relevance
“…Although the 210 liver samples tested in our study form a biased sample population, as all of these birds either had died or were euthanized due to the severity of their injuries or illness, the prevalence of BFDV infection was comparable to that seen in previous studies. We detected BFDV DNA in 30 % of 20 Victorian crimson rosellas, while another recent study detected BFDV DNA in 34.5 % of 84 wild crimson rosellas in southeastern Australia [9]. Likewise Raidal et al [5]reported a seroprevalence of 41-94 % within wild cockatoo flocks in New South Wales in the early 1990s using a haemagglutination inhibition assay [5], while we detected BFDV DNA in 67.7 % of 31 Victorian cacatuids.…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…Although the 210 liver samples tested in our study form a biased sample population, as all of these birds either had died or were euthanized due to the severity of their injuries or illness, the prevalence of BFDV infection was comparable to that seen in previous studies. We detected BFDV DNA in 30 % of 20 Victorian crimson rosellas, while another recent study detected BFDV DNA in 34.5 % of 84 wild crimson rosellas in southeastern Australia [9]. Likewise Raidal et al [5]reported a seroprevalence of 41-94 % within wild cockatoo flocks in New South Wales in the early 1990s using a haemagglutination inhibition assay [5], while we detected BFDV DNA in 67.7 % of 31 Victorian cacatuids.…”
Section: Discussionmentioning
confidence: 74%
“…It has been implicated as a cause of wild parrot declines in Australia and Mauritius [9,11,22]. Host-switching occurs at a high rate across divergent Psittaciformes, with rare spillovers into distantly related non-psittacine bird species also reported [6,10,11,16].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations